The interaction of acidification and warming on the South African abalone, Haliotis midae, and the potential for mitigation in aquaculture - Lester, Nina Catherine (Department of Biological Sciences, 2022)
The South African abalone, Haliotis midae, is an economically important species. H. midae is the largest of the five endemic abalone species in South Africa and is especially valuable in Asian markets. Over-fishing, increased predation (due a geographical shift in lobster populations), and prolific poaching of this commercially valuable species have depleted natural populations. Commercial abalone aquaculture began as a means to meet the market demand for H. midae and currently accounts for 77 % of South Africa's aquaculture revenue. Despite marked growth in this industry over the past decade, further increases will be challenged by the predicted threat of climate change, particularly ocean acidification. Calcifying organisms, such as abalone, are particularly susceptible to the impacts of ocean acidification and its resultant alteration in seawater carbonate chemistry. Most calcifying organisms display reduced calcification and growth in response to ocean acidification, with possible alterations to acid-base regulation, development, gonadal maturation and behaviour, as well as reduced larval and gamete survival. A further potential challenge to abalone aquaculture is global warming. The effects of temperature change depend on the organism's level of sensitivity, taxonomy, distribution and life history. The distribution of H. midae ranges from Saldanha Bay (cool-temperate) to Riet Point (warm-temperate), with the majority of commercial aquaculture production occurring in Hermanus (cool-temperate). Abalone aquaculture facilities will need to adapt to these environmental changes and assess potential mitigation strategies. This study investigated the long-term (12 months) impact that ocean acidification and warming will have on the South African abalone, Haliotis midae, by incorporating the natural variability of seawater pH and temperature in Hermanus. Ambient seawater retained natural pH and temperature variability and acidified seawater was offset to natural pH variability using CO2/O2 diffusion and a data-logger-relay system to incorporate local-scale variability of seawater in the abalone farm, where this experiment was based. A multi-parameter approach was used to investigate the effects of reduced pH (- 0.4 from ambient) and warming (+ 1.5 °C from ambient) on abalone growth, spawning patterns, acid-base regulation, shell growth, morphology, shell strength and mineralogy over 12 months. This study also investigated the potential use of Ulva (Chlorophyta) as a mitigational tool to ameliorate acidified seawater, by photosynthetic carbon dioxide uptake, in a flow-through aquaculture system on a South African abalone farm. This study assessed the effects of seaweedtreated seawater on abalone growth, spawning patterns, acid-base regulation, shell growth, morphology, shell strength and mineralogy over 12 months in comparison to ambient and acidified seawater. Ocean acidification conditions resulted in a decrease in H. midae haemolymph pH and an increase in pCO2 (indicative of uncompensated respiratory acidosis), which resulted in reduced growth (whole-, muscle-, and shell-mass) and an alteration in spawning patterns. Acidification conditions also altered shell shape (smaller area with a wider shape) and significantly reduced shell strength. Warming conditions were within the thermal optimum ranges for H. midae and did not significantly affect abalone growth; however warming did bring about significant changes in Condition Factor, shell shape, and strength over time and shifted acid-base regulation towards a more stable status. The combined impact of warming and acidification were similar to the effects of reduced pH alone, with the exception of effects on acid-base regulation (severe uncompensated respiratory acidosis) and shell shape (lengths and widths were moderately increased). Ocean acidification and warming conditions, singularly and in combination, had no significant impact on shell mineralogy (percentage weight of aragonite, and aragonite and calcite crystal diameter). Bio-mitigation of acidified seawater by Ulva increased abalone wet weight, GBI, shell length, shell width and shell area in comparison to acidified conditions. Warming, caused by Ulva cultivation, resulted in similar effects on abalone shell growth and acid-base regulation as those exposed to warmed conditions alone. However, ambient and acidified seaweed-treated seawater caused a significant reduction in abalone muscle mass during summer months in comparison to abalone grown in ambient seawater. This decrease in muscle mass occurred concurrently with a decline in Ulva yield (due to photoinhibition), suggesting an interactive effect of Ulva (under stressor conditions) and abalone which needs to be studied further. The findings of this thesis are of particular concern for the South African abalone industry as ocean acidification conditions are likely to result in slower abalone growth, increased cultivation time to reach market-size, and reduction in quality of abalone (as the shells are more easily damaged). This study highlights the importance of incorporating local-scale, natural variability into ocean acidification and warming studies to guide management practices for cultivation and protection of this valuable species. The incorporation of natural seawater variability highlights an overexaggerated effect of warming on abalone exposed to constant-temperature experiments. Although predicted increases in seawater temperature (+ 1.5 °C) are within the optimal thermal ranges for H. midae in Hermanus, warming could pose a risk for aquaculture sites in warm-temperate areas of the South African coast. This thesis provides feedback on a potential mitigation strategy for abalone farms, with options for improvements in design as well as further mitigational options in the face of climate change. This is the first study to assess the effects of long-term elevated CO2 and warming on H. midae, and the first to incorporate long-term, natural variability into climate change research for any species outside of a laboratory.